Overexpression of a newly identified d‐amino acid transaminase in Mycobacterium smegmatis complements glutamate racemase deletion. Issue 2 (7th December 2017) - Mortuza, Roman; Aung, Htin Lin; Taiaroa, George; Opel‐Reading, Helen K.; Kleffmann, Torsten; Cook, Gregory M.; Krause, Kurt L.
Summary: Glutamate racemase (MurI) has been proposed as a target for anti‐tuberculosis drug development based on the inability of Δ murI mutants of Mycobacterium smegmatis to grow in the absence of d‐glutamate. In this communication, we identify Δ murI suppressor mutants that are detected during prolonged incubation. Whole genome sequencing of these Δ murI suppressor mutants identified the presence of a SNP, located in the promoter region of MSMEG_5795. RT‐qPCR and transcriptional fusion analyses revealed that the Δ murI suppressor mutant overexpressed MSMEG_5795 14‐fold compared to the isogenic wild‐type. MSMEG_5795, which is annotated as 4‐amino‐4‐deoxychorismate lyase (ADCL) but which also has homology to d‐amino acid transaminase (d‐AAT), was expressed, purified and found to have d‐AAT activity and to be capable of producing d‐glutamate from d‐alanine. Consistent with its d‐amino acid transaminase function, overexpressed MSMEG_5795 is able to complement both Δ murI deletion mutants and alanine racemase (Δ alr ) deletion mutants, thus confirming a multifunctional role for this enzyme in M. smegmatis . Abstract : Deletion of glutamate racemase ( murI ) in M. smegmatis is initially bacteriostatic, but following prolonged incubation, a revertant phenotype consistently develops, which is due to overexpression of MSMEG_5795. This gene is currently annotated as 4‐amino‐4‐deoxychorismate lyase, but in this study, it is found to have d‐amino acid transaminase activity. The MSMEG_5795 gene, with overexpression, is able to rescue deletion mutants of either glutamate racemase or alanine racemase and could play an important role in mycobacterial cell wall metabolism, and should be reannotated as a d‐amino acid transaminase.